(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Femicide, as a legal term, is not defined in international instruments. However, this crime is found in the criminal legislation of some countries. Many states have included femicide as either intentional homicide or serious intentional injury, often considering it as an aggravating circumstance of the offense. This study explores the concept of femicide, along with relevant provisions at the international and European levels. It also examines pertinent cases from the jurisprudence of the European Court of Human Rights concerning femicide.